SHARING TAKJIL, BREAKING THE BREAK TOGETHER AND SUPPORTING THE SERDANG BEDAGAI STUDENTS ASSOCIATION ORPHANAGE WITH RADJA PUBLIKA AND RADJA PUSTAKA LHOKSEUMAWE NORTH ACEH 2024 - Rico Nur Ilham; Irada Sinta; Muammar Khaddafi; Likdanawati; Hamdiah; Sutriani (RADJA PUBLIKA, 2024)
Sharing takjil, breaking the fast together, and providing donations to children from orphanages are social initiatives that aim to strengthen relationships between individuals and provide assistance to those in need, especially children from orphanages, realizing the concern of lecturers and administrators of Radja Publica Grub andIKMA SERGAI in increasing the sense of social concern for others, instilling human values ​​so that the next generation has a strong sense of empathy. This is basedLaw Number 4 of 1979, LN.19979-32 concerning child welfare, article 4 (1) states that